Bakerwal Sheep: Migratory breed of Jammu and Kashmir - Khan, Nusrat Nabi; Ahmad Ganai, Nazir; Ahmad, Tavsief; Majid, Ruksana; Shanaz, Syed (Indian Farming, 2022)
The present study was carried out to collect and consolidate all the information available on Bakerwal sheep. They are medium-sized animals, with a typical Roman nose. The fleece which is coarse and open is generally white, although coloured fleeces are occasionally observed. The rams are horned and the ewes are polled. The horns were brown to creamy and curved. The adult weight of Bakerwal sheep ranges from 40–51 kg in males and 29–35 kg in females. These are seasonal breeders and the ewes are mostly bred during their autumn alpine camps or while returning to villages on migration camps